Problems and Solutions for Faith Education in the Digital Era at Smp Baitul Arqam Qur'anic Science Sumedang - Sundari, Susan; Heris Hermawan, Acep (Yayasan Mentari Madani, 2024)
Faith education has an important role in holistic student development. The development of digital technology brings profound changes to education. In this digital era, there are many problems faced in the learning process in schools, resulting in an increasing complexity of faith education problems. This article discusses the main problems faced in organizing faith education at SMP Baitul Arqam Qur'anic Science Sumedang in the digital era. The problem of faith education faced is the influence of digitalization on the character, morals and formation of students' self-identity. Efforts are made to deal with these problems by limiting the use of smartphones in students, educating students about the use of smartphones wisely, innovating and creativity in the learning process of faith education, and optimizing digital technology as a tool to increase understanding of faith for students